Analysis of the Application of Occupational Safety and Health in Structural Work in the South Sulawesi Education Quality Assurance Institute (LPMP) Building Renovation Project - Marlina Pasarong; Junus Mara; Helen Adry Irene Sopacua (Paulus Civil Engineering Journal, 2021)
The appIication off occupationaI heaIth and sahfety (K3) is never dry in the context of the scientific ocean. Either in an academic research or in a practical study. K3 issues are constantly raised in the discussion of academic papers, be it journals or final assignments. Of course, the "intersection" with the "knife" which is called "research". On this occasion, the focus of the researcher was the construction project work in the renovation of the South Sulawesi Education Quality Assurance Institute (LPMP) building using quantitative descriptive methods. Namely describing the application of K3 and analyzing the constrain ts in implementing K3 in the project. Statistical methods are used to determine the percentage of respondents' answers or calculated by formulas. The resuIts off research that hass been carriedt out in the building renovation project off the Education Quality Assurance Institute (LPMP) of South Sulawesi regarding the implementation of Occupational Safety & Health (K3) are carried out quite well. The obstacle to the implementation of Occupational Safety & Health is the lack of awareness and knowledge of workers about Occupational Safety and Health (K3). In addition, the company is also less consistent in implementing Occupational Health and Safety.